Apoptosis induction in human prostate cancer cells related to the fatty acid metabolism by wogonin-mediated regulation of the AKT-SREBP1-FASN signaling network. (November 2022) - Sun, Yuening; Guo, Wenjing; Guo, Yongjian; Lin, Zhangxing; Wang, Dechao; Guo, Qinglong; Zhou, Yuxin
Abstract: Prostate cancer (PCa) cells exploit cellular metabolic reprogramming as their survival advantage, especially aberrant lipid signaling and metabolism. Although recent studies deemed that PCa tends to rely on lipid fuel in comparison with aerobic glycolysis, the relationship between lipid metabolism and cancer growth remains unknown. We demonstrated that wogonin, a naturally occurring mono-flavonoid, could induce apoptosis of PCa cells in vivo and in vitro . Mechanistically, 100 μM wogonin significantly increased the expression of proteins related to the fatty acid synthesis and accumulation as a result of stimulation of AKT phosphorylation and nuclear accumulation of sterol regulatory element-binding protein 1 (SREBP1). The wogonin-induced up-regulation of fatty acid synthase (FASN) promoted fatty acid synthesis and storage, while increased oxidation in mitochondria driven by carnitine palmitoyl-transferase 1A (CPT1A) resulted in the loss of mitochondrial membrane potential and reactive oxygen species (ROS) accumulation, ultimately inducing apoptosis in DU145 and 22Rv1 cells. In vivo, 100 mg/kg of wogonin (i.v.) significantly repressed tumor growth without any obvious toxicity in the PCa xenograft model. In short, we proved that wogonin regulated the fatty acid metabolism and induced apoptosis by activating the AKT-SREBP1-FASN signaling network in human PCa cells, and it exhibited potent anti-tumor effects both in vivo and vitro . Thus it might be a promising candidate for the development of anti-cancer drugs. Graphical abstract: Image 1